Call Centre: Ecrasez l’infame! Review of Jamie Woodcock’s Working the Phones: Control and Resistance in Call Centres - Zielińska, Justyna; Zych, Jacek (Praktyka Teoretyczna, 2018)
This is a review of Jamie Woodcock’s study of the call centre as a workplace, Working the Phones. The text discusses the methodology of co-research and the results of Woodcock’s engagement with forms of control and resistance in call centres.